EVALUATION OF PIE IN SUNFLOWER POWER OF CHICKENS CUT ALMOST HILLBILLY - M. R. Silva; J. F. Costa Júnior; G. M. A. Silva; L. B. Freiria; C. M. S. Santos; R. K. Silveira; M. S. M. Pinheiro (Scientific Electronic Archives, 2015)
The goal in performing this study was to determine the best level of sunflower cake in feeding broilers semi-rustic-line Label Rouge. In the experiment were acquired with 180 birds a day old, distributed in a completely randomized design (CRD) with four treatments, five replicates and nine animals per experimental unit. The diets of the birds were based on the ingredients ground corn, soybean meal, core and different percentages of inclusion of sunflower cake: 0%, 5%, 10% and 15%. The parameters used in the experiment were the average daily weight gain, total weight gain, viability, feed intake, feed efficiency ratio and productive. At eighty-day-old chicks were assessed and it was observed that the performance of the birds was not affected by the introduction of sunflower cake in the diet. You can include up to 15% of sunflower cake in the feed of broilers semi-rustic without causing production losses.